Volumetric comparison of autogenous bone and tissue-engineered bone replacement materials in alveolar cleft repair: a systematic review and meta-analysis. Issue 6 (July 2018) - Kamal, M.; Ziyab, A.H.; Bartella, A.; Mitchell, D.; Al-Asfour, A.; Hölzle, F.; Kessler, P.; Lethaus, B.
Abstract: The goal of reconstruction of the alveolar cleft in patients with cleft lip and palate is to improve the quality of tissue, the structural stability, and increase the volume of bone. This study is a systematic review with meta-analysis of volumetric bony filling using autogenous bone and various tissue-engineered bone substitutes. We made an electronic search on MEDLINE, EMBASE, SCOPUS, WEB OF SCIENCE, "grey" publications (materials and research produced by organisations outside traditional channels for commercial or academic publishing and distribution), and relevant cross references according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies that reported the outcomes of volumetric grafting were included in the meta-analysis. Of 1276 studies, 26 were included in the meta-analysis. Pooled analysis of 25 studies that used autogenous bone showed a significant reduction in the volume of the cleft equivalent to 62.0% bone fill (95% CI 54.3 to 69.6), in contrast to 10 studies that used a tissue-engineered material and reported bone filling of 68.7% (95% CI 54.5 to 82.8). The estimated sizes of pooled effects across studies showed that there was no significant difference between the two major intervention groups (p value 0.901). Our statistical analysis showed that autogenous bone grafts did not differ significantly from tissue-engineered materials in their ability to fill clefts. Systematic review registration : International Prospective Register of Systematic Reviews, PROSPERO (CRD42017065045).